Truncated Creativity: Child Abuse Influence on Creative Capacity. Art Therapy with Neurotic Patients - Duran Coll, Magdalena (Arteterapia. Papeles de arteterapia y educación artística para la inclusión social, 2021)
Trough this brief study I intend to draw a link between certain creative blockages and childhood experiences related to psychological and/or verbal abuse, by one or both of main attachment figures. The study is based on patients in art therapy with a neurotic profile in the process of personal growth. The aftermath of child abuse can lead to difficulties with creative processes in adults, especially regarding their own ability to value their productions, value themselves, and find meaning and purpose in life. Oftentimes in the sessions it appears how introjected abuse is installed as a hyper-critical instance blocking the flow of creativity and introducing a loss of hope and meaning.This study is based on real cases with art therapy patients in individual sessions, in private clinical practice, undergoing long treatments lasting from 30 to 80 sessions. The cases are exposed through vignettes, which illustrate the different stages of the study text. The approach used in this study integrates my knowledge and experience between psychodynamic Art therapy and Gestalt Therapy, along with relevant studies on complex trauma suffered in childhood and its effects in adulthood.
Keywords: Art Therapy; Trauma; Creative Blockings; Creativity; Neurosis